2012
DOI: 10.1002/trtr.01128
|View full text |Cite
|
Sign up to set email alerts
|

Blogging as a Means of Crafting Writing

Abstract: The purpose of this article is to explore ways in which blogs can support literacy communities while developing a writing community. Examples of how a classroom teacher uses blogs to strengthen the writing process is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…In his research, it was found that the use of technological advances had numerous positive effects on learners' writing skill and it also proved to engage the students more than the traditional paper and pen writing. Another research conducted by Lacina and Griffith (2012) also confirms the above findings. Their research showed that students' writing is better improved through the use of technological advances such as blogging and digital storytelling.…”
Section: Discussionsupporting
confidence: 76%
“…In his research, it was found that the use of technological advances had numerous positive effects on learners' writing skill and it also proved to engage the students more than the traditional paper and pen writing. Another research conducted by Lacina and Griffith (2012) also confirms the above findings. Their research showed that students' writing is better improved through the use of technological advances such as blogging and digital storytelling.…”
Section: Discussionsupporting
confidence: 76%
“…There is no doubt that a contemporary approach to using journals in the classroom should incorporate technology. For example, blogging and online journals engage students, bolster reflective learning, enhance experiential learning, create a community of writers, and provide multimodal opportunities for self‐expression (Karchmer‐Klein & Shinas, ; Lacina & Griffith, ; Zawilinski, ).…”
Section: Journaling In the Classroom: A Suggested Frameworkmentioning
confidence: 99%
“…There is no doubt that a contemporary approach to using journals in the classroom should incorporate technology. For example, blogging and online journals engage students, bolster ref lective learning, enhance experiential learning, create a community of writers, and provide multimodal opportunities for self-expression (Karchmer-Klein & Shinas, 2012;Lacina & Griffith, 2012;Zawilinski, 2009). Google Classroom, for example, includes Google Docs, a multifaceted web-based word processor that does not require the student to save, allows multiple writers to edit a document simultaneously, and can be revised in real time from any internet browser (Technology for Teachers and Students, 2018).…”
Section: Addressing Technologymentioning
confidence: 99%
“…Lenhart and Fox (2006) reported that approximately 12 million Americans maintain a blog and 57 million read them. These blogs are particularly popular with upper elementary through middle school students (Lacina & Griffith, 2012). Blogs can have many purposes.…”
Section: 1)mentioning
confidence: 99%